Сыни тұрғыдан ойлауды үйретудің тиімділігі - Абдиркенова, А.Қ.; Әбдісалық, Қ.А. (My University, 2016)
The significance of critical thinking is one of the modules of the teachers development program. The practical use of key ideas. Facilitate development of creative students abilities considering the methods of critical thinking.
Keywords: learning; teaching; critical thinking